2022
DOI: 10.2166/wst.2022.137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag/ZnO-AC composite photocatalyst: spectroscopic investigation, parameter optimization, synergistic effect and performance enhancement for cost-effective photocatalytic degradation of phenols and dyes

Abstract: A ternary photocatalyst composite-Silver decorated on ZnO supported with activated carbon (Ag/ZnO-AC) was investigated for the synthesis, characterization and UV assisted photocatalytic degradation of phenols and dyes present in wastewater. XPS and TEM revealed the elemental composition and formation of ternary Ag/ZnO-AC composite. Different operational parameters including the effect of calcination temperature, catalyst dose, initial concentration of pollutant and the effect of H2O2 and ethanol were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a study conducted by Ma, et al ( 2015), this reaction occurred at a temperature of 360˚C which was indicated by the appearance of the compound Zn2OCl2.2H2O identified by the sharp peak of XRD at 2θ is 11.2˚ and detected ZnO peak at 2θ between 30˚ to 40˚ followed up to 59.7•, this indicates the decomposition of Zn2OCl2.2H2O that can occur further when the temperature is increased to 600˚C, where the evaporation of ZnCl2 occurs with the following reaction taking place on eq. ( 4) and (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Ma, et al ( 2015), this reaction occurred at a temperature of 360˚C which was indicated by the appearance of the compound Zn2OCl2.2H2O identified by the sharp peak of XRD at 2θ is 11.2˚ and detected ZnO peak at 2θ between 30˚ to 40˚ followed up to 59.7•, this indicates the decomposition of Zn2OCl2.2H2O that can occur further when the temperature is increased to 600˚C, where the evaporation of ZnCl2 occurs with the following reaction taking place on eq. ( 4) and (5).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of waste paper originates from wood or cotton pulp, primarily composed of cellulose fibers (constituting 90-99%), which are rich in carbon, possess a distinctive pore structure, and feature functional groups such as carboxylic and hydroxyl groups [4]. Addressing the mitigation of pollutants carried by effluents requires effective adsorbents like zeolites, activated carbon, activated alumina, silica gel, among others [5]. Activated carbon is particularly favored due to its commendable performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation